Seaweed Extracts to Control Postharvest Phytopathogenic Fungi in Rocha Pear - Eloísa Toledo; Carina Félix; Tânia F. L. Vicente; Ana Augusto; Rafael Félix; Bernardo Toledo; Joana Silva; Carina Trindade; Délio Raimundo; Marco F. L. Lemos (Journal of Fungi, 2023)
Fungal infections cause losses amounting to between 20 and 25% of the fruit industry’s total outcome, with an escalating impact on agriculture in the last decades. As seaweeds have long demonstrated relevant antimicrobial properties against a wide variety of microorganisms, extracts from Asparagopsis armata, Codium sp., Fucus vesiculosus, and Sargassum muticum were used to find sustainable, ecofriendly, and safe solutions against Rocha pear postharvest fungal infections. Alternaria alternata, Botrytis cinerea, Fusarium oxysporum, and Penicillium expansum mycelial growth and spore germination inhibition activities were tested in vitro with five different extracts of each seaweed (n-hexane, ethyl acetate, aqueous, ethanolic, and hydroethanolic). An in vivo assay was then performed using the aqueous extracts against B. cinerea and F. oxysporum in Rocha pear. The n-hexane, ethyl acetate, and ethanolic extracts from A. armata showed the best in vitro inhibitory activity against B. cinerea, F. oxysporum, and P. expansum, and promising in vivo results against B. cinerea using S. muticum aqueous extract were also found. The present work highlights the contribution of seaweeds to tackle agricultural problems, namely postharvest phytopathogenic fungal diseases, contributing to a greener and more sustainable bioeconomy from the sea to the farm.